RANCANG BANGUN DIAGNOSA PENYAKIT AYAM PEDAGING (BROILER) DAN PETELUR DENGAN METODE CERTAINTY FACTOR BERBASIS ANDROID - Angga Dwi Cahyana; Fatsyahrina Fitriastuti; Yumarlin Yumarlin MZ (Universitas Janabadra, 2020)
Chicken farming is a profitable business for both breeding broilers and native chickens. In the chicken farm business, disease is one of the risks that must be faced by breeders. Expert systems are Artificial Intelligence which make special extensions to specialization of knowledge to solve a problem. Human Expert is someone who is an expert in a certain field of science. The inference method used is Certainty Factor, which has more than one rule and consists of several premises that are connected with AND or OR. The data entered is in the form of symptoms leading to a conclusion, namely the conclusion of the disease suffered and providing solutions regarding treatment and prevention suggestions based on the visible symptoms of the chicken's physical appearance. Design and build expert systems capable of identifying diseases and providing information on how to deal with them to chicken breeders. In the results of the trial, it can be concluded that the application can run well and provides an alternative in using android-based broiler and laying disease diagnosis systems and chicken farm owners can diagnose the disease early before the disease spreads to healthy chickens. Keywords: Expert System, Chicken Disease, Certainty Factor